Relapsing optic neuritis: a multicentre study of 62 patients. (June 2014) - Benoilid, Aurélien; Tilikete, Caroline; Collongues, Nicolas; Arndt, Carl; Vighetto, Alain; Vignal, Catherine; de Seze, Jérôme
Background: Optic neuritis (ON) may be the first symptom of a central nervous system demyelinating, systemic or infectious disease but few patients experience recurrent episodes and have a negative workup. Objective: This disorder, named relapsing optic neuritis (RON), is poorly described in the literature and still presents a particular challenge in diagnosis and management. Methods: We describe the clinical, laboratory, magnetic resonance imaging (MRI) and disability course of RON in a French cohort of 62 patients, based on a multicentre, retrospective, observational study. Results: In our cohort, we identified two distinct groups of RON patients. The first is characterised by relapsing inflammatory optic neuritis (RION, 68%), which is non-progressive, whereas the second presented as a chronic relapsing inflammatory optic neuritis (CRION, 32%), which is progressive. We have noted more cases with steroid dependence in the CRION group than the RION group (42% vs 10%). The long-term visual prognosis was more severe in CRION patients and neuromyelitis optica-immunoglobulin G (NMO-IgG)-positive patients. Conclusion: RON is likely a separate entity corresponding to an autoimmune disease that differs from multiple sclerosis (MS), NMO and vasculitis. We provide a new classification system based on a better understanding of RON which could allow an improved management by early treatment of poor prognosis forms.